The naval officer's guide - McComas, Lesa A., 1958-; Mack, William P., 1915- (Naval Institute Press, 2011)
The Naval Officer's Guide is a collection of information and advice intended primarily for officers in the US Navy, but it also provides a valuable introduction to the sea services for officers of other uniformed services, members of the U.S. interagency community, naval history buffs, or anyone interested in learning more about the Navy.